Frontline. The real CSI [videorecording (DVD)] - Bartos, Leah (PBS Distribution, 2012)
An episode of "Frontline," examining the tools and techniques used in forensic science to solve criminal cases, discussing inconsistencies and how forensic evidence is presented in the court room, and describing such specific cases as the murder trial of Casey Anthony, the FBI's investigation into the Madrid terrorist bombing, and capital cases in rural Mississippi.